Pengambilan Keputusan Petani Padi dalam Menggunakan Combine Harvester di Desa Kepuhkajang Kecamatan Perak - Wahyuningrum, Widya; Soedarto, Teguh; Setiawan, Risqi Firdaus (Universitas Galuh, 2025)
Post-harvest activities in rice farming are very noteworthy because the choice of harvesting process and time will affect the quantity and quality obtained and quality obtained. Farmers are faced with several factors that factors into consideration for the decision to use an agricultural technology. Objective of this research is to analyze the factors that influence decision making of farmers in using combine harvester during harvesting. The location of this research is in Kepuhkajang Village, Perak District, Jombang Regency. The research method used is quantitative method. The sampling method used is using probability sampling technique with cluster random sampling method with the number of research samples sampling technique with cluster random sampling method with the number of research samples the number of research samples is 87 farmers who are divided into two criteria, namely 61 farmers who are users of combine harvester and 26 farmers who do not use combine harvester. Data collection methods used were filling out questionnaires by respondents, interviews, and observations. respondents, interviews, and observation. Data analysis was conducted using the method of binary logistic regression analysis with the help of SPSS software. The result of of this research is that the land area variable and the income variable have a significant and positive effect on farmers' decision making in farming. significantly and positively on farmers' decision making in using combine harvester using a combine harvester with a value of 0.012 and 0.005 respectively. Meanwhile, the variables of age, number of family members, level of education, and length of farming do not have a significant farming do not significantly affect the decision-making of farmers in using a combine harvester.